First International Conference on Mars Polar Science and Exploration: held at the Episcopal Conference Center at Camp Allen, Texas - Fisher, D. A. (David A.); Rice, J. W. (James W.); Clifford, Stephen Mark, 1952-; orcid:0000-0003-0771-1713 (Lunar and Planetary Institute, 1998)
Articles about the geology of the Martian Polar regions were presented, and analogs from Earth's geology were also presented. Presentations also were given about the probable contents of the Martian polar caps. sponsored by Geological Survey of Canada . [and others] organizers Stephen Clifford, David Fisher, James Rice compiled by Lunar and Planetary Institute.